Urgensi Pembentukan Badan Penyelesaian Sengketa Konsumen di Kabupaten Bekasi Provinsi Jawa Barat - Nopiana, Medi; Maulana, Agus (Eqien - Jurnal Ekonomi dan Bisnis, 2017)
This research aims to formulate and to analyze the urgency of the establishment of Consumer Dispute Resolution Body (BPSK) in Regency of Bekasi. The method of analysis uses descriptive analysis of both qualitative and quantitative. Meanwhile, the method of data collection is done through literature studies and in-depth interviews. The results show that the urgency of the formation of BPSK in Regency of Bekasi is based on variety of reasons. First, BPSK as a government agency is established to respond to the mandate of Act No. 8 1999 to form the agency in each regency. Secondly, BPSK is formed to anticipate the momentum of the ASEAN Economic Community. Thirdly, it is also founded to react to the improvement of economic development in Regency of Bekasi, which is accompanied by the increasing level of prosperity and the level of community awareness of the rights of workers as consumers. Fourth, BPSK is constructed based on the experience of other regions which shows that consumers are in dire need of a neutral government body formed to protect the interests of consumers if they get unfair treatment from business actors. As the same time, business actors also require the same body that can objectively and impartially handle cases involving their business activities. Keywords: Consumer Protection, BPSK, Regency of Bekasi